Study of referral pattern for psychiatric evaluation in psychiatric OPD in a rural tertiary care hospital - Shaikh, Muhammad Abdul Kayum; Ali, Md Zulfikar; Islam, Md Saiful; Mokhlesuzzaman, AKM (KYAMC Journal, 2013)
Health includes both physical and psychological well being of an individual. There is strong chance that every physical illness has psychological component and in many cases psychological disorders present with somatic symptoms; so psychiatric referral is very important to the proper management of a patient. The aim of this study was to find out the pattern of referral from different outpatient departments in a tertiary level hospital in rural setting of Bangladesh. In this descriptive study total 237 patients were evaluated in 7 months period and most of the diagnoses were anxiety disorders (40%), major depressive disorder (35%) and somatoform disorders (17%). Departments of medicine (cardiology 34%, internal medicine 28% and neurology 26%) referred most of the patients than the surgical or gynecological departments. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13517 KYAMC Journal Vol.2(1) 2011 pp.128-131